2015
DOI: 10.3329/fmcj.v9i2.25681
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Appendicectomy: A Comparison of Primary Outcome

Abstract: Abstract:Currently, laparoscopic appendectomy is widely practiced for the management of acute appendicitis. It is not clear whether open or laparoscopic appendectomy is more appropriate. Our aim was to compare the safety and the advantages of laparoscopic versus open appendectomy in a prospective study. 102 patients were participated in this study. The group 1 patients were subjected to laparoscopic appendectomy [LA], whereas the group 2 patients were subjected to open appendectomy [OA]. 46 patients included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The mean age difference was not statistically significant (p>0.05) between two groups. In study of Rahman et al 14 showed the mean age was found 31.5±6.1 years open group and 29.8±5.2 years in laparoscopic group. The difference was not statistically significant (p>0.05) between two groups.…”
Section: Figure-i: Organisms Isolated From Ssi Wounds Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean age difference was not statistically significant (p>0.05) between two groups. In study of Rahman et al 14 showed the mean age was found 31.5±6.1 years open group and 29.8±5.2 years in laparoscopic group. The difference was not statistically significant (p>0.05) between two groups.…”
Section: Figure-i: Organisms Isolated From Ssi Wounds Discussionmentioning
confidence: 89%
“…Incisional/port site hernia was found 4% in OA group and 2% in LA group. In study of Rahman et al 14 showed in LA group one patient developed mild surgical emphysema, resolved spontaneously. Wound or port site infection is significantly higher in open group (p=0.019).…”
Section: Figure-i: Organisms Isolated From Ssi Wounds Discussionmentioning
confidence: 93%